Structural Reliability of Tall Buildings Under Wind Loads with Tuned Mass Damper Fluid Inerters - Fitzgerald, Breiffni (My University, 2025)
This study investigates the reliability of tall buildings subjected to dynamic across- wind loading, focusing on the Tuned Mass Damper Fluid Inerter (TMDFI). While existing literature emphasises the effectiveness of TMDFI in mitigating seismic hazards, research on its reliability regarding wind hazards remains limited. A wind-sensitive benchmark 76- storey building is modeled to compare the performance of the TMDFI against a traditional tuned mass damper (TMD) and an uncontrolled structure. A Monte Carlo Simulation (MCS) approach comprising 31,500 simulations is employed to assess reliability under uncertain damping ratios and varying turbulence intensities at reference wind speeds of 20 to 40 m/s. Key performance metrics, including peak acceleration and root mean squared (RMS) displacement responses, are derived through spectral analysis in the frequency domain. Results indicate that the TMDFI offers superior reliability, allowing an additional 6–7 m/s in reference velocity before reaching significant failure at the ISO limit state. Peak acceleration and RMS displacement are reduced by up to 64% to the uncontrolled structure. The TMDFI consistently outperforms both the TMD and uncontrolled configurations across all turbulent cases and wind velocities examined.
PUBLISHED
Keywords: inerter, tuned mass damper, vibration control, tall building; Smart & Sustainable Planet; Structural Dynamics; Structural Engineering; Structural Safety